Examiner variability in caries diagnosis of selected UPCD-oral diagnosis faculty members - Grajo, Dennis Adriane R.
In improving the dental health of the population and providing the most conservative yet appropriate treatment, a consistent diagnosis of the presence of a disease must be made. Since it is in dental schools such as the UP College of Dentistry that dentists (starting as undergraduates) first learn about the carious process, clinical guidelines on diagnosis should reflect consistency and uniformity among instructors who teach it. The primary aim of this study was to assess/investigate the variability in the caries detection skills of selected UPCD faculty members in the Oral Diagnosis (OD) Section. Randomly selected OD faculty members (N=6) blindly observed and examined all the 1st and/or 2nd molars of 6 pre-dental students posing as regular patients of the college. Fisher Exact Test was used to assess the inter-examiner reproducibility (calibration) while Cohen's Kappa Statistic was used to assess the intra-examiner reproducibility (consistency) both of which were tested at .05 significance level. Results showed that majority of the selected examiners exhibited higher degree of inter-examination calibration during the 1st exam than on the 2nd exam. Intra-examiner consistency on the other hand ranged from good to substantial agreement with one examiner exhibiting an "at random" agreement. No direct relationship can be attributed between the calibration and consistency of the examiners and their demographic data (age, years in practice, educational level and type of practice).